A fearsome doubt : an Inspector Ian Rutledge mystery - Todd, Charles (Todd, Charles. Inspector Ian Rutledge novels., 2003)
Seven years after sending Ben Shaw to the gallows for the brutal murders of elderly women, Inspector Ian Rutledge is approached by Shaw's widow, who claims that her husband had been innocent, and sets out to uncover the truth.